Strategies to enhance THz harmonic generation combining multilayered, gated, and metamaterial-based architectures - Ali Maleki; Moritz B. Heindl; Yongbao Xin; Robert W. Boyd; Georg Herink; Jean-Michel Ménard (Light: Science & Applications)
Abstract Graphene has unique properties paving the way for groundbreaking future applications. Its large optical nonlinearity and ease of integration in devices notably makes it an ideal candidate to become a key component for all-optical switching and frequency conversion applications. In the terahertz (THz) region, various approaches have been independently demonstrated to optimize the nonlinear effects in graphene, addressing a critical limitation arising from the atomically thin interaction length. Here, we demonstrate sample architectures that combine strategies to enhance THz nonlinearities in graphene-based structures. We achieve this by increasing the interaction length through a multilayered design, controlling carrier density with an electrical gate, and modulating the THz field spatial distribution with a metallic metasurface substrate. Our study specifically investigates third harmonic generation (THG) using a table-top high-field THz source. We measure THG enhancement factors exceeding thirty and propose architectures capable of achieving a two-order-of-magnitude increase. These findings underscore the potential of engineered graphene-based structures in advancing THz frequency conversion technologies for signal processing and wireless communication applications.